1981
DOI: 10.1007/bf00262020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin on growth of cultured human arterial smooth muscle cells

Abstract: The effect of insulin (10--10 000 mU/1) on the proliferation of cultured human arterial smooth muscle cells was studied. Smooth muscle cells were cultivated by explanation. Cells from the third to the fifth subculture were used. Proliferation was studied by growth curve experiments. Insulin stimulated cell proliferation in all concentrations (p less than 0.001). Growth was however stimulated more by a medium containing 10% fetal calf serum. The highest concentration of insulin produced only 35% of the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
74
2
6

Year Published

1981
1981
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(82 citation statements)
references
References 9 publications
0
74
2
6
Order By: Relevance
“…Similarly, some previous studies have shown an inverse association between insulin levels and arterial elasticity. 5,9,31 The mechanisms by which insulin level may effect arterial distensibility are not well elucidated but may include the effects of insulin, promoting vascular wall smooth muscle hypertrophy 37 and collagen tissue synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some previous studies have shown an inverse association between insulin levels and arterial elasticity. 5,9,31 The mechanisms by which insulin level may effect arterial distensibility are not well elucidated but may include the effects of insulin, promoting vascular wall smooth muscle hypertrophy 37 and collagen tissue synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that chronic hyperinsulinaemia might induce vasoconstrictor responses since insulin stimulates vascular smooth muscle cell growth in animals and man [49,50]. Therefore, an insulin-induced structural change in resistance vessels may be responsible for increased peripheral resistance or lead to increased sensitivity to vasoconstrictor agonists.…”
Section: Discussionmentioning
confidence: 99%
“…t has been reported that hyperinsulinemia is an independent risk factor for ischemic heart disease (1) and induces greater vascular smooth muscle cell proliferation in experimental models (2,3). Insulin resistance with hyperinsulinemia is associated with hypertension, glucose intolerance, obesity, and dyslipoproteinemias of low HDL cholesterol levels or hypertriglyceridemias, which are wellknown risk factors for coronary artery disease (4 -6).…”
mentioning
confidence: 99%